1993
DOI: 10.1177/153944929301300203
|View full text |Cite
|
Sign up to set email alerts
|

Pressure Sore Prophylaxis in Elderly Patients Using Slab Foam or Customized Contoured Foam Wheelchair Cushions

Abstract: In a modified sequential trial, we randomly assigned 288 elderly patients, who were assessed to be at high risk of pressure sores (Norton score ≤14), to use slab foam or customized contoured foam cushions in their wheelchairs for 3 months. A total of 359 sores developed in 169 (68%) of the 248 at-risk patients who completed the study. The sores were mostly of the persistent erythema level (57%) in severity and took an average of 28 days to heal. No significant differences were found in the overall incidence, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Individuals who cannot independently reposition tend to be at the greatest risk for ulcer development 10. Several studies have indicated that the use of pressure-redistributing wheelchair cushions designed to maintain tissue integrity will reduce the incidence of sitting-induced pressure ulcers 5, 11, 7, 12, 13, 14…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Individuals who cannot independently reposition tend to be at the greatest risk for ulcer development 10. Several studies have indicated that the use of pressure-redistributing wheelchair cushions designed to maintain tissue integrity will reduce the incidence of sitting-induced pressure ulcers 5, 11, 7, 12, 13, 14…”
Section: Introductionmentioning
confidence: 99%
“…10 Several studies have indicated that the use of pressureredistributing wheelchair cushions designed to maintain tissue integrity reduce the incidence of sitting-induced pressure ulcers. 5,7,[11][12][13][14] In a systemic review of the evidence from studies investigating interventions to prevent pressure ulcers, 4 the 59 randomized controlled trials (RCTs) selected for review enrolled a total of 13,845 patients, 2,367 (17.1%) in longterm care (LTC). Fifty-one of these studies targeted mobility (1,866 patients in LTC), five targeted nutrition, and three targeted skin health.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have monitored interface pressures in real-time under the buttocks [18,[40][41][42][43][44][45][46][47][48], but these values have been proven to be much smaller than those from the loading situation in the muscle itself, especially near the IT [49]. Other studies have adopted a much more accurate approach, estimating stresses in the muscles under the IT using FE and complex calculations, at the cost of immediacy and portability [4,36,39].…”
Section: Introductionmentioning
confidence: 99%
“…If pressure from sitting obstructs capillary blood flow, ischemia results and pressure ulcers can develop within 2 to 6 hours (Lyder, 2003;Stekelenburg, 2005). If peak pressures exceed 60 mmHg, the incidence of pressure ulcers increases (Conine et al, 1993). Pressure ulcers are most common superficial to the sacrum, coccyx and ischial tuberosities (Cuddigan et al, 2001;Richardson and Meyer, 1981).…”
Section: Introductionmentioning
confidence: 99%